FORMATION OF SOCIALLY ACTIVE CIVIL EDUCATION OF STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS - Qoʻrgʻonboyev Shukrillo Maxmudillo oʻg’li; Mingboyev Boburjon (American Journals Publishing, 2024)
Approaches related to the idea of the essence of the content of education of a citizen, an active citizen, an individual approach, approaches related to the development of active civil initiatives, education of students as a harmonious person with intellectual potential, pedagogical conditions for the development of socially active civil competence, knowledge of socially active civil education, civil duty, obligation and rights, compliance with it, in legal relations, there has been thought about methods of shaping qualities such as treatment and possession of a legal culture.
Keywords: Education, citizenship, intellectual potential, socially active citizenship, civic competence, initiative, technology, method, problem, educational technology, science, educational system.